Noah's ark : pop-up book (Nashville, Tennessee : Clever Factory, 2013)
Simple text and pop-up illustrations tell the story of Noah and the flood.
Board book.
Keywords: Noah (Biblical figure) -- Juvenile literature; Bible stories